Adobe Premiere Pro CC : 2018 release - Jago, Maxim, ....- ([San Francisco] : Adobe Press, 2018)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe Premiere Pro CC (2018 release) choose Adobe Premiere Pro CC Classroom in a Book (2018 release) from Adobe Press. The 18 project-based lessons in this book show users step-by-step the key techniques for working in Premiere Pro. Learn to edit video in Adobe Premiere Pro CC 2018 and get the most out of your workflow. Take a project from beginning to end and learn to organize media, add audio, create transitions, produce titles, and add effects. Take your projects further by sweetening and mixing sound, compositing footage, adjusting color, using advanced editing techniques, managing projects, working with 360 video for VR headsets, animating graphics, exporting, and much more. The online companion files include all the necessary assets for readers to complete the projects featured in each chapter as well as ebook updates when Adobe releases relevant new features for Creative Cloud customers. All buyers of the book get full access to the Web Edition: a Web-based version of the complete ebook enhanced with video and multiple-choice quizzes.